428 The role of virtual visits in COVID-19 cardiovascular patients. (8th December 2021) - Di Iorio, Martina; Mei, Mariachiara; Bernardini, Alessia; Magnocavallo, Michele; Vetta, Giampaolo; Piro, Agostino; Mariani, Marco Valerio; Giunta, Giuseppe; Quaglione, Raffaele; Chimenti, Cristina; Trivigno, Sara; Mancone, Massimo; et al.
Abstract: Aims: The outbreak of the Coronavirus Disease 2019 (COVID-19) pandemic forced a reorganization of the healthcare system. In order to prevent potential risk of exposure, virtual visit (VV) has been implemented in the treatment and follow-up of COVID-19 patients with cardiovascular diseases. The aim of this study is to evaluate the feasibility and efficacy of VV in the management of post COVID-19 cardiovascular patients. Methods and results: We enrolled all patients with cardiovascular comorbidities tested negative for Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) and discharged from our Cardiology Department from January 2021 to June 2021. We scheduled a VV after 30 days from discharge to check the clinical status of the patients, optimize therapy, and establish a Follow-up protocol. Blood pressure, arterial oxygen saturation, heart rate and body weight were registered. To evaluate the patients' satisfaction of VV, a questionnaire was administered. We performed 25 VVs in the study period; the mean age of patients was 67.5 ± 15.6 and male were 15 (65.2%). The mean duration of VV was 25.9 ± 4.6 min. The caregiver had an active role in nine (36%) cases. No urgent/emergent in‐person examinations were performed. A high degree of patient satisfaction was reached and VV was preferred to in-person evaluation. Conclusions: VV visit was useful to Follow-up post COVID-19 cardiovascular patients. A high degree of patient satisfaction was reached without jeopardizing quality of care.